A clinical interpretation of shame regulation in maladaptive perfectionism. (1st February 2019) - Schalkwijk, Frans; Van Someren, Eus J.W.; Wassing, Rick
Abstract: Maladaptive perfectionism, a transdiagnostic personality trait, is associated with depression. Shame has been associated with depressive disorders and to negatively impact its treatment. Interestingly, maladaptive perfectionism and maladaptive shame regulation strategies might be both expressions of an internalizing personality style. We applied forward and backward stepwise linear regression modeling to explain maladaptive perfectionism by association of shame coping styles in a highly powered cross-sectional study of 1436 participants. Maladaptive perfectionism was shown to have significant positive associations with the two internalizing coping styles attacking the self, and withdrawing, and negative associations with adaptive coping. Furthermore, a significant positive interaction effect was shown for the two internalizing coping styles. Our research shows that participants who adopt maladaptive perfectionism, internalize the pain of shame. Clinically, this is especially relevant during treatment: the patterns of maladaptive perfectionism must come into the open, the client feels exposed and, consistent with his shame regulation style, shame grows. Our research might account for the negative responsiveness of perfectionism to brief therapies for depression: there may not be enough focus on and time for working through the evoked shame. Highlights: Specifically internalizing shame regulation explains maladaptive perfectionism. No such association with externalizing shame regulation or shame-proneness We plea for focus on working though evoked shame in psychotherapeutic practice.